Unveiling Community Involvement Gaps in Toddler Stunting Recovery - Jihan Andita Firdausi; Isna Fitria Agustina (Universitas Muhammadiyah Sidoarjo, 2024)
Stunting remains a significant issue in Larangan Village, Candi District, Sidoarjo Regency, largely due to inadequate community participation in nutrition-related activities and low public awareness of posyandu services. This qualitative study analyzes community involvement in stunting recovery and identifies barriers to effective engagement. Data from interviews, observations, and documentation with key village figures indicate that while contributions from the village government, cadres, and midwives have improved, community enthusiasm and motivation remain low due to poor awareness and socio-economic challenges. Enhancing community education, improving socio-economic conditions, and fostering better organizational collaboration are crucial for improving stunting recovery efforts. Highlights: Community Engagement: Assessing local stakeholder contributions for toddler nutrition improvement. Awareness Gap: Identifying public knowledge gaps on posyandu services for stunting recovery. Socio-economic Barriers: Exploring economic challenges hindering community health initiative participation. Keywords: Stunting, Community Participation, Posyandu Services, Nutrition, Socio-economic Factors